Are Biofuels the Culprit? OPEC, Food, and Fuel - Hochman, Gal; Rajagopal, Deepak; Zilberman, David (American Economic Review, 2010)
The food commodity price boom of 2003–2008 was the most notable in the past several decades, having a substantial impact on global economic activity. It affected developing nations by impacting real output, the balance of payments, government budgetary positions and, most important, the well being of the very poor. High commodity prices also affected developed countries, by transmitting business cycle disturbances and creating inflationary pressures. Several recent studies tried to identify and quantify the factors that caused the food commodity price boom of 2003–2008 (see, for instance, Isabel Vansteenkiste 2009). These studies suggest that one key factor is growth in demand, which, since the 1980s, has outpaced growth in supply. Other studies argued that biofuel is the culprit, since it increases demand for staple crops (see, for instance, Donald Mitchell 2008). All these studies, however, assumed competitive markets and did not consider the impact of biofuel on energy costs to farmers. Moreover, they ignored the Organization of Petroleum Exporting Countries (OPEC). These studies leave us perplexed regarding the true impact of biofuel on food commodity prices— was it or was it not an important contributor to the recent food commodity boom? We believe that to answer this question, the interactions between energy and food must be modeled and OPEC introduced, and the impact of biofuels compared with other factors that are argued by the literature to be important. This paper aims to analyze the multiple contributions of energy and biofuels to the increase Are Biofuels the Culprit? OPEC, Food, and Fuel